Preventable mortality after common urological surgery: failing to rescue?. (19th August 2014) - Sammon, Jesse D.; Pucheril, Daniel; Abdollah, Firas; Varda, Briony; Sood, Akshay; Bhojani, Naeem; Chang, Steven L.; Kim, Simon P.; Ruhotina, Nedim; Schmid, Marianne; Sun, Maxine; Kibel, Adam S.; et al.
Abstract : Objective: To assess in‐hospital mortality in patients undergoing many commonly performed urological surgeries in light of decreasing nationwide perioperative mortality over the past decade. This phenomenon has been attributed in part to a decline in 'failure to rescue' (FTR) rates, e.g. death after a complication that was potentially recognisable/preventable. Patients and Methods: Discharges of all patients undergoing urological surgery between 1998 and 2010 were extracted from the Nationwide Inpatient Sample and assessed for overall and FTR mortality. Admission trends were assessed with linear regression. Logistic regression models fitted with generalised estimating equations were used to estimate the impact of primary predictors on over‐all and FTR mortality and changes in mortality rates. Results: Between 1998 and 2010, an estimated 7 725 736 urological surgeries requiring hospitalisation were performed in the USA; admissions for urological surgery decreased 0.63% per year ( P = 0.008). Odds of overall mortality decreased slightly (odds ratio [OR] 0.990, 95% confidence interval [CI] 0.988–0.993), yet the odds of mortality attributable to FTR increased 5% every year (OR 1.050, 95% CI 1.038–1.062). Patient age, race, Charlson Comorbidity Index, public insurance status, as well as urban hospital location were independent predictors of FTR mortality ( P < 0.001). Conclusion: A shift from inpatient to outpatient surgery for commonly performed urological procedures has coincided with increasing rates of FTR mortality. Older, sicker, minority group patients and those with public insurance were more likely to die after a potentially recognisable/preventable complication. These strata of high‐risk individuals represent ideal targets for process improvement initiatives.